PREVENTION OF DEVIANT BEHAVIOUR OF MINORS IN THE TERRITORY OF THE STAVROPOL KRAI: A MODERN LEGAL AND INSTITUTIONAL ANALYSIS - O. Pogozheva; S. Pliev (Гуманитарные и юридические исследования)
Prevention and suppression of tort, delinquency and crime among adolescents is the most important national task of any state. Instability in the development of society, socio-economic, political / geopolitical, cultural changes affect the value orientations of young people, their personal attitudes and sometimes provoke a «drift» of the teenager's personality into an unfavorable environment. Today, the negative influence of the media, social networks, computer network games especially determines the deviant behavior of adolescents. The article presents an analysis of statistical data on juvenile delinquency and delinquency in Russia and the Stavropol Territory, which suggests that the effectiveness of regulatory and institutional support for adolescents in the Stavropol Territory is at a high level. The Stavropol Territory forms its regulatory and institutional framework on the basis of legislative acts of the Russian Federation regulating activities to prevent child neglect and juvenile delinquency, bases regional legislation on the Constitution of the Russian Federation, generally recognized principles and norms of international law. ... An analysis of the normative and institutional system for the prevention of deviant behavior among minors both in Russia and in the Stavropol Territory revealed a wide interdepartmental community that functions effectively and contributes to the formation of the infrastructure of other social services, new type institutions that provide social services to families and adolescents, which, of course, , creates conditions for the full development of the personality of adolescents.